2004
DOI: 10.1111/j.1600-6143.2004.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

A Seroprevalence Study of West Nile Virus Infection in Solid Organ Transplant Recipients

Abstract: West Nile virus (WNV) causes severe neurological disease in less than 1% of infections. However, meningoencephalitis may be more common in immunosuppressed transplant patients. In 2002, a WNV outbreak occurred in our region. To determine the spectrum of disease of community acquired WNV infection and assess public health behavior patterns in transplant recipients, we carried out a seroprevalence study. Patients were enrolled from outpatient transplant clinics in October 2002 and sera were screened for WNV. Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 20 publications
0
59
1
1
Order By: Relevance
“…In addition, transplant recipients should be educated regarding the risk of WNV infection and the use of preventive measures, especially as a recent study performed in Canada found poor rates of compliance among SOT recipients with regard to WNV protection (214).…”
Section: Infections Caused By West Nile Virusmentioning
confidence: 99%
“…In addition, transplant recipients should be educated regarding the risk of WNV infection and the use of preventive measures, especially as a recent study performed in Canada found poor rates of compliance among SOT recipients with regard to WNV protection (214).…”
Section: Infections Caused By West Nile Virusmentioning
confidence: 99%
“…28 People over 50 years of age (particularly those of 60-89 years of age) are at highest risk (20-fold increase) for developing meningo encephalitis, with a slightly higher incidence among males ( Figure 3). 3,29,31 Immunosuppressed recipients of transplanted organs have an increased risk of developing neuroinvasive disease (estimated at up to 40-fold increase in some studies), 18,32 and when disease develops it is often more severe than in immunocompetent individuals. 33 Other immunosuppressed individuals might be at higher risk, but this has not been shown conclusively.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Compared with the general population, where the infection rate for WNV was 5 per 100,000, the rate in transplant recipients was 200 per 100,000 (P < .001) [99]. A seroprevalence study found a 0.25% seroprevalence and a resultant 40% risk of meningoencephalitis in a transplant patient with community acquired WNV [100]. Similar studies of immunocompetent persons estimate the risk of meningoencephalitis to be less than 1%.…”
Section: Less Common But Significant Viral Infections After Transplanmentioning
confidence: 94%